Error Analysis of Writing Verbs in Discussion Text - Dadang Solihat; Diah Novianti (English Review: Journal of English Education, 2015)
The objective of this study is to find out the error types of writing verbs in students‟ discussion texts and to identify the factors causing verb errors at the fourth semester students of English major in University of Kuningan. The subject of this study is 20 students. The limitation of the problem is to classify the students‟ errors based on Linville„s error types in writing verbs, there are subject-verb agreement errors, verb tense errors, and verb form errors. This research is using qualitative method by collecting data from documents, questionnaires, and interviews. The result showed that the highest error which most students made is subject-verb agreement. Its frequency is 105 errors or 78.95 %. The second common error is verb form with 15 errors or 11.28 %. The third common error is verb-tense with 13 errors or 9.77 %. The factors causing verb errors are interlingual factor and intralingual or developmental factor. It is influenced by the students‟ lack of knowledge and understanding of the use of verbs.Key words: subject-verb agreement error, verb tense error, verb form error, interlingual factor, intralingual or developmental factor